ChemInform Abstract: Approach to the Core Structure of abeo‐Abietanes and Gibberellins via Stork—Danheiser Sequence Followed by Friedel—Crafts Alkylations. Issue 25 (3rd June 2013) - Kakde, Badrinath N.; Bhunia, Subhajit; Bisai, Alakesh
Abstract Stork—Danheiser reaction of bicyclic vinylogous esters (I) with alkoxy‐substituted arylmagnesium bromides followed by intramolecular Friedel—Crafts alkylation of the resulting cyclohexenones (III) offers a short synthesis of [6, 5, 6] carbocyclic frameworks.